Preliminary Monitoring and Observation of Fuel Cell Temperature Characteristics by Using NiCr-NiSi Thin-Film Thermocouple - Zhihui Liu; Bohao Chang; Jinzhe Li; Yingyu Chen; Xingshu Wang; Zeren Rong; Zixi Wang; Wanyu Ding (Micromachines)
This study presents the calibration methodology of NiCr-NiSi thin-film thermocouples and evaluates their application in real-time temperature monitoring and characterization of fuel cell thermal behavior. Experimental results reveal that the Seebeck coefficients of the NiCr-NiSi thin films remain stable after multiple calibration cycles, indicating good reliability and repeatability. Furthermore, the thermocouples demonstrate an ultrafast response time of less than 15 microseconds and reach thermal equilibrium within 200 microseconds under transient thermal inputs. These characteristics enable accurate and rapid temperature measurement of fuel cell plates up to 100 °C, which is critical for maintaining the safe and efficient operation of fuel cells.